Potential of trophy hunting to create incentives for wildlife conservation in Africa where alternative wildlife-based land uses may not be viable - Lindsey, P.A; Alexander, R; Frank, L.G; Mathieson, A; Romañach, S.S (Animal conservation, 2006)
There is a lack of consensus among conservationists as to whether trophy hunting represents a legitimate conservation tool in Africa. Hunting advocates stress that trophy hunting can create incentives for conservation where ecotourism is not possible. We assessed the hunting preferences of hunting clients who have hunted or plan to hunt in Africa (n=150), and the perception among African hunting operators (n=127) of client preferences at two US hunting conventions to determine whether this assertion is justified. Clients are most interested in hunting in well-known East and southern African hunting destinations, but some trophy species attract hunters to remote and unstable countries that might not otherwise derive revenues from hunting. Clients are willing to hunt in areas lacking high densities of wildlife or attractive scenery, and where people and livestock occur, stressing the potential for trophy hunting to generate revenues where ecotourism may not be viable. Hunting clients are more averse to hunting under conditions whereby conservation objectives are compromised than operators realize, suggesting that client preferences could potentially drive positive change in the hunting industry, to the benefit of conservation. However, the preferences and attitudes of some clients likely form the basis of some of the problems currently associated with the hunting industry in Africa, stressing the need for an effective regulatory framework.